Evanghelia apocrifă a Martei Petreu: identităţi elective – corporalitate afectivă - Daniela Moldoveanu (Revista de Istorie și Teorie Literară)
The poetic imagery of Marta Petreu’s overcrowds the world of her verse with death visions and captures and, at the same time, points out to second degree, intellectualized states of mind which are meant not to reveal the pure emotion of the poet, but represent the processing of this emotion into the melting pot-brain of the poem. Her poems intend to be both authentic and concept-based. Desperation, fury, curses, physical and psychological pain, obsession, hysteria, all of these represent the state of mind the reader adopts. And this happens mainly because Marta Petreu proves to be a skilled, self-centered orchestrator of inner degradation. The concept is Marta Petreu’s ontological space where she isolates herself looking for semantic and linguistic uniqueness among other feminine Romanian voices of her generation. For her, even the ever searched for, analyzed, classified love remains deeply conflicting and generates several interrogations that raise the appetite for selfdevouring.